Brassicas cultivars classification in relation to resistance to diamondback moth and to the presence of glucosinolates - Thuler, Robson Thomaz; Bortoli, Sergio Antonio De; Campo, Clara Beatriz Hoffmann (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the effect of cabbage and kale cultivars on the diamondback moth biology; to analyze the plant chemical composition in relation to glucosinolates and to apply the multivariate analysis to classify cultivar resistance. Trials were conduct using: green cabbage cultivar Chato-de-quintal and hybrid Midori; purple cabbage Roxo precoce and purple hybrid TPC00682; kale cultivar Georgia (susceptibility standard) and hybrid HS20. The pest biological characteristics evaluated were: viability and the length of the larval and pupal period, sex ratio, female fertility, adult longevity and the length and viability of the egg phase; also it was calculated the corrected reproductive potential index (CRP). Pearson correlation was obtained, and the grouping and main components of multivariate analysis were applied. Sinigrin and other glucosinolates were evaluated by liquid chromatography. 'Georgia', 'Roxo' and HS20 hybrids were classified as highly susceptible; 'Roxo precoce' and Midori hybrid, as susceptible, and 'Chato-de-quintal' as moderately resistant to diamondback moth. Multivariate analyses provided a better way to classify cultivars in relation to different resistance degrees. Brassica genetic materials evaluated do not present sinigrin.